Peran Guru Pendidikan Agama Kristen Menurut Injil Matius 18:6-11 Dan Hubungannya Dengan Upaya Guru Dalam Membimbing Rohani Siswa/i SMA Negeri 1 Kotapinang - Imeldawati, Tiur; Tarigan, Berta; Manalu, Johannes Cerdas (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The teacher is the central figure in the implementation of Christian Religious Education in schools. The Bible contains a lot of information related to the implementation of teaching activities, where Jesus is the main figure in the education sector with many teachings conveyed to the people both in the synagogue and in various other places. And specifically, this research focuses on the text of Matthew 18:6-11, by selecting the variable role of Christian Religious Education teachers and their relationship with the efforts made by Christian religious teachers to guide the spirituality of students being taught and the research location is in SMA Negeri 1 Kotapinang. This research is motivated by the situation and the presence of students in the research location which is still far from expectations. Through mixed research methods, this research was carried out by studying the exegesis of the text of Matthew 18:6-11 and its implementation in the school was followed by quantitative research procedures on research respondents. The discussion and results are explained clearly, and it is hoped that the results of this research can bless teachers who become Christian education practitioners wherever they are.Â Keywords: role, teacher, christianity, spiritual guidance, Matthew